ÙØ§Ø¹Ù„ÙŠØ© Ø¨Ø±Ù†Ø§Ù…Ø¬ Ù…Ù‚ØªØ±Ø Ù„ØªÙ†Ù…ÙŠØ© Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø´Ù‡Ø§Ø¯Ø©Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„Ù…Ø§Ù„ÙŠØ²ÙŠØ© - Ø¹ØµØ§Ù… Ø¹Ù„ÙŠ Ù…Ù†ØµÙˆØ± Ø§Ù„Ø£Ø´ÙˆØ; Ù†ÙˆØ± Ø¹Ø§Ø´Ù‚ÙŠÙ† Ø¨Ù†Øª Ø¹Ø«Ù…Ø§Ù†; Ø§Ù„Ø³ÙŠØ¯ Ù…ØÙ…Ø¯ Ø³Ø§Ù„Ù… (Kota Bengkulu, Provinsi Bengkulu, Indonesia, 2023)
Ù…Ù„Ø®Øµ Ø§Ù„Ø¨ØØ« Ø§Ø³ØªÙ‡Ø¯Ù Ø§Ù„Ø¨ØØ« ØªÙ†Ù…ÙŠØ© Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„Ø´Ù‡Ø§Ø¯Ø© Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„Ù…Ø§Ù„ÙŠØ²ÙŠØ© Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ± Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ Ø¹Ù† Ø·Ø±ÙŠÙ‚ Ø¨Ø±Ù†Ø§Ù…Ø¬ Ù…Ù‚ØªØ±Ø ÙŠÙ‚ÙˆÙ… Ø¹Ù„Ù‰ Ø·Ø±Ø§Ø¦Ù‚ ØªØ¯Ø±ÙŠØ³ ØØ¯ÙŠØ«Ø© Ù„Ù…Ø§Ø¯Ø© Ø§Ù„Ø¨Ù„Ø§ØºØ©ØŒ ÙˆÙ‚Ø¯ Ø§Ø®ØªØ§Ø± Ø§Ù„Ø¨Ø§ØØ« ÙƒÙ„ÙŠØ© Ø§Ù„Ù„ØºØ© ÙˆØ§Ù„Ø¯ÙŠÙ† Ø§Ù„Ø³Ù„Ø·Ø§Ù† Ø£Ø¨Ùˆ Ø¨ÙƒØ±Ù€ Ø¨ÙƒØ§Ù†ØŒ Ø¨Ù‡Ø§Ù†Ø¬Ø› Ù„ØªÙƒÙˆÙ† Ù…Ø¬ØªÙ…Ø¹Ø§ Ù„Ø¨ØØ«Ù‡ØŒ ÙˆØªÙƒÙˆÙ†Øª Ø¹ÙŠÙ†Ø© Ø§Ù„Ø¨ØØ« Ù…Ù† ( 112 ) Ø·Ø§Ù„Ø¨Ø§ØŒ ÙˆØªÙ… ØªÙ‚Ø³ÙŠÙ… Ø§Ù„Ø¹ÙŠÙ†Ø© Ø¥Ù„Ù‰ Ù…Ø¬Ù…ÙˆØ¹ØªÙŠÙ† Ø¥ØØ¯Ø§Ù‡Ù…Ø§ ØªØ¬Ø±ÙŠØ¨ÙŠØ© ÙˆØ§Ù„Ø£Ø®Ø±Ù‰ Ø¶Ø§Ø¨Ø·Ø© Ø› ÙˆÙ„ØªØÙ‚ÙŠÙ‚ Ø£Ù‡Ø¯Ø§Ù Ø§Ù„Ø¨ØØ« Ø§Ø³ØªØ®Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ« Ø§Ù„Ø£Ø¯ÙˆØ§Øª Ø§Ù„Ø¢ØªÙŠØ©:1. Ø¥Ø¹Ø¯Ø§Ø¯ Ù‚Ø§Ø¦Ù…Ø© Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© Ø§Ù„Ù„Ø§Ø²Ù…Ø© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø´Ù‡Ø§Ø¯Ø© Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„Ù…Ø§Ù„ÙŠØ²ÙŠØ© (STAM Â ).2. Ø¥Ø¹Ø¯Ø§Ø¯ Ø§Ø³ØªØ¨Ø§Ù†Ø© Ù„Ù…Ø¹Ø±ÙØ© Ø§ØªØ¬Ø§Ù‡Ø§Øª Ø§Ù„Ø·Ù„Ø§Ø¨ Ù†ØÙˆ Ù…Ø§Ø¯Ø© Ø§Ù„Ø¨Ù„Ø§ØºØ©ØŒ ÙˆÙ‚ÙŠØ§Ø³ Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© Ù„Ø¯ÙŠÙ‡Ù…ØŒ ÙˆÙ…Ø¹Ø±ÙØ© Ø£Ø³Ø¨Ø§Ø¨ Ø¶Ø¹ÙÙ‡Ù… ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ù…Ù† ÙˆØ¬Ù‡Ø© Ù†Ø¸Ø±Ù‡Ù….3. Ø¨Ø±Ù†Ø§Ù…Ø¬ ØªÙ†ÙÙŠØ°ÙŠ Ù…Ù‚ØªØ±Ø Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø·Ø±Ø§Ø¦Ù‚ ØªØ¯Ø±ÙŠØ³ ØØ¯ÙŠØ«Ø© Ù„Ù„Ø¨Ù„Ø§ØºØ© Ù„ØªÙ†Ù…ÙŠØ© Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ (STAM Â ).4. Ø§Ø®ØªØ¨Ø§Ø± ØªØØµÙŠÙ„ÙŠ Ù„Ù‚ÙŠØ§Ø³ Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ (STAM Â ) Ø¨Ø¹Ø¯ ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„Ø¨Ø±Ù†Ø§Ù…Ø¬ Ø§Ù„Ù…Ù‚ØªØ±ØØ› Ù„Ù…Ø¹Ø±ÙØ© Ù…Ø¯Ù‰ ÙØ§Ø¹Ù„ÙŠØ© Ù‡Ø°Ø§ Ø§Ù„Ø¨Ø±Ù†Ø§Ù…Ø¬.ÙˆÙ‚Ø¯ Ø£Ø¸Ù‡Ø±ØªÙ†ØªØ§Ø¦Ø¬Ø§Ù„Ø¯Ù‘Ø±Ø§Ø³Ø©ÙˆØ¬ÙˆØ¯ÙØ±ÙˆÙ‚Ø°Ø§ØªØ¯Ù„Ø§Ù„Ø©Ø¥ØØµØ§Ø¦ÙŠÙ‘Ø©Ø¹Ù†Ø¯Ù…Ø³ØªÙˆÙ‰Ø§Ù„Ø¯Ù„Ø§Ù„Ø© (Î±= 0.05) Ø¨ÙŠÙ† Ø§Ù„Ù…Ø¬Ù…ÙˆØ¹ØªÙŠÙ†ØªØ±Ø¬Ø¹ Ø¥Ù„Ù‰ ÙØ§Ø¹Ù„ÙŠØ©Ø§Ù„Ø¨Ø±Ù†Ø§Ù…Ø¬Ø§Ù„Ù…Ù‚ØªØ±ØÙ„ØµØ§Ù„ØØ§Ù„Ù…Ø¬Ù…ÙˆØ¹Ø©Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠØ©ÙˆÙÙŠØ¶ÙˆØ¡Ù†ØªØ§Ø¦Ø¬Ø§Ù„Ø¨ØØ«ØŒØ£ÙˆØµØªØ§Ù„Ø¯Ø±Ø§Ø³Ø©Ø¨Ø§Ø¹ØªÙ…Ø§Ø¯Ø§Ù„Ø¨Ø±Ù†Ø§Ù…Ø¬Ø§Ù„Ù…Ù‚ØªØ±Ø Ø§Ù„Ø°ÙŠ ÙŠØ³ØªÙ†Ø¯ Ø¹Ù„Ù‰ Ø·Ø±Ø§Ø¦Ù‚ ØªØ¯Ø±ÙŠØ³ ØØ¯ÙŠØ«Ø© Ù„Ù„Ø¨Ù„Ø§ØºØ©.Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙØªØ§ØÙŠØ©: ( Ø§Ù„ÙØ§Ø¹Ù„ÙŠØ© Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€ Ø§Ù„Ø¨Ø±Ù†Ø§Ù…Ø¬ Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€ Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€ Ø§Ù„Ø´Ù‡Ø§Ø¯Ø© Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„Ù…Ø§Ù„ÙŠØ²ÙŠØ©).Â Abstract :The research aims to develop the rhetorical skills of students of the Malaysian high religious certificate who speak non-Arabic, through a proposed program based on modern teaching methods for rhetoric, The researcher chose the College of Language and Religion, Sultan Abu Bakr, Bekan, Pahang; To be a community for his research, and the research sample consisted of (112) students. To achieve the objectives of the research, the researcher used the following tools: 1. Preparing a list of rhetorical skills required for students of the Malaysian Higher Religious Certificate (STAM). 2. Preparing a questionnaire to find out students' attitudes towards rhetoric, measure their rhetorical skills, and find out the reasons for their weakness in these skills from their point of view. 3. A proposed executive program based on modern teaching methods for rhetoric to develop rhetorical skills among students (STAM). 4. An achievement test to measure the rhetorical skills of (STAM) students after applying the proposed program; To find out the effectiveness of this program. The results of the study showed that there were statistically significant differences at the significance level (Î± = 0.05) between, The two groups are due to the effectiveness of the proposed program in favor of the experimental group and in the light of the research results, the study was recommended, By adopting the proposed program, which is based on modern teaching methods of rhetoric.Keywords: Efficacy, Program, Rhetorical skills, Malaysian high religious certificate.